2021
DOI: 10.1002/jbm.a.37261
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical performance of collagen gels is dependent on purity, α1/α2 ratio, and telopeptides

Abstract: This article describes the compositional, mechanical, and structural differences between collagen gels fabricated from different sources and processing methods. Despite extensive use of collagen in the manufacturing of biomaterials and implants, there is little information as to the variation in properties based on collagen source or processing methods. As such, differences in purity and composition may affect gel structure and mechanical performance. Using mass spectrometry, we assessed protein composition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Thinner fibers will generate more bonds per unit mass and be more likely to form a percolated network than thicker fibers for the same total concentration of collagen ( 51 ). An excellent example is reconstituted collagen gels, which have relatively small fiber diameters (∼50 nm) ( 52 ) and have a modulus at relatively low mass concentrations (3 mg/ml). In contrast, since collagen fibers in cartilage are thicker (∼1 μm), the concentration of collagen required for rigidity percolation in tissue extracellular matrix is significantly larger (∼90 mg/ml) than that in reconstituted collagen gels.…”
Section: Discussionmentioning
confidence: 99%
“…Thinner fibers will generate more bonds per unit mass and be more likely to form a percolated network than thicker fibers for the same total concentration of collagen ( 51 ). An excellent example is reconstituted collagen gels, which have relatively small fiber diameters (∼50 nm) ( 52 ) and have a modulus at relatively low mass concentrations (3 mg/ml). In contrast, since collagen fibers in cartilage are thicker (∼1 μm), the concentration of collagen required for rigidity percolation in tissue extracellular matrix is significantly larger (∼90 mg/ml) than that in reconstituted collagen gels.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, with acid extraction methods (telo) this telopeptide region is left intact. While both types of collagen have been proven useful for 3D gel synthesis and cell culture, studies have shown that telocollagen produces mechanically stronger hydrogels than atelocollagen possibly due to the presence of higher number of cross-linking sites within the telopeptide region of the collagen molecule. ,, …”
Section: Discussionmentioning
confidence: 99%
“…In addition, differences in isolation methods (i.e., acid extraction vs enzymatic digestion) yield collagen protein with structural disparities with (telo) and without (atelo) the telopeptide ends which can also impact the properties of CMA. While prior studies have investigated the effects of different species and isolation techniques on properties of collagen hydrogels, how these innate structural differences impact the physiochemical properties of CMA is unknown. In addition, changes in compositional and mechanical properties of CMA can also influence cell behavior and its applicability as a bioink for 3D printing applications.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is a ubiquitous component of the native extracellular matrix and exhibits a unique triplex‐helix fibril structure 22,23 . Collagen is widely used for tissue regeneration because of its low antigenicity and excellent biocompatibility and biodegradability 24‐26 .…”
Section: Introductionmentioning
confidence: 99%
“…Collagen is a ubiquitous component of the native extracellular matrix and exhibits a unique triplex-helix fibril structure. 22,23 Collagen is widely used for tissue regeneration because of its low antigenicity and excellent biocompatibility and biodegradability. [24][25][26] In this study, we constructed a collagen-based bioactive nerve graft that physically bridges a transected nerve and serves as a CNTF carrier.…”
Section: Introductionmentioning
confidence: 99%